(untitled) (European Journal of Economics, Finance and Business Development, 2026)
The effective management of credit risk remains one of the most important factors influencing the stability, competitiveness, and sustainable development of banking systems. This study examines modern directions for improving credit risk management mechanisms in Uzbekistan’s banking system through the analysis of foreign experience and national practice. The research explores international approaches to credit risk management, including risk-based supervision, credit portfolio diversification, macroprudential regulation, and the development of credit information infrastructures. In addition, the current state of credit risk management practices in Uzbekistan is assessed, and existing institutional and regulatory challenges are identified. The study applies comparative, analytical, and benchmarking methods to evaluate the applicability of international experience to the national banking environment. Based on the findings, practical recommendations are proposed to strengthen supervisory effectiveness, improve credit risk assessment procedures, enhance credit information systems, and increase the resilience of commercial banks. The results indicate that the adaptation of advanced foreign practices to national conditions can contribute significantly to improving credit risk management mechanisms and supporting the long-term stability of Uzbekistan’s banking sector.